Development, Release, and Popularization of the Novel Inbred Rice Variety "Mini Shail" for the Aman Season in Bangladesh - Hasan, Md. Moniruzzaman; Islam, Md. Ariful; Akter, Tanbin; Md. Saiful Islam, Shahed (International Journal on Food, Agriculture and Natural Resources, 2025)
Rice is the major staple crop of Bangladesh, and alone it occupies about 78% of the arable land of the country. However, the production level is not enough to meet the demands of food security for the growing population. The present study is on the development, evaluation, release, and promotion of the new inbred rice variety "Mini Shail" (IR14A-09) for the Aman season, targeting the basic demand for food security. We conducted multi-location testing across Bangladesh, where eight advanced rice lines emanating from IRRI were put to the test. "Mini Shail" outperformed others in yield amongst its competitors' check types of BRRI dhan39 and BRRI dhan49 varieties. Through proposed variety trial (PVT) at various locations, its improved yield was confirmed, while distinctness, uniformity, and stability (DUS) testing underlined its distinctiveness on morphological characteristics. Besides, "Mini Shail" had better consumer acceptance due to slender grain and superior cooking properties with an amylose content appropriate for non-sticky rice. The National Seed Board of Bangladesh named the "Mini Shail" as Rabi dhan1 after obtaining sufficient experiences from field experiments. This variety increases yield, enhances disease tolerance, reduces production cost, and hence assures food security and profit to farmers in Bangladesh. The effective development and marketing of "Mini Shail" demonstrate that cooperation in plant breeding goes a long way in solving agricultural problems.